Measurement of Seawater Flow-Induced Erosion Rates for Iron Surfaces using Thin Layer Activation Technique - Kambali, Imam; Suryanto, Hari (Journal of Engineering and Technological Sciences, 2016)
The laboratory-scale erosion-corrosion testing facility at BATANâs Center for Radioisotope and Radiopharmaceutical Technology (PTRR) in Serpong was employed to simulate flow-induced corrosion of iron surfaces. Surface loss rates were measured by a nuclear technique called thin layer activation (TLA) analysis. A 10-MeV proton beam generated from a typical CS-30 cyclotron was used to produce 56Co radionuclide layers on iron surfaces via a 56Fe(p,n)56Co nuclear reaction. The labeled iron specimens were then exposed to circulating seawater simulated in BATANâs flow-induced corrosion test facility. The experimental results indicated that the TLA technique was able to measure a very low flow-induced erosion rate of 0.91Â±0.3 Âµm/hr. There was no significant difference in the measured surface loss rates between the remaining activity method and the concentration method. The iron surface loss in seawater was lower than that of the same material in HCl solution observed in earlier studies.